Wind-induced motion of tall buildings : designing for habitability - Kwok, Kenny C. S.; Burton, Melissa D.; Abdelrazaq, Ahmad K. (American Society of Civil Engineers, 2015)
This book presents an overview of current research on occupant response to motion in tall buildings. This state-of-the-art report describes the physiology and psychology of the human perception of motion and explains the factors that can be used to characterize a building's movement. The authors summarize the results of field studies and motion simulator experiments that examine human perception of and tolerance for building motion. They survey the serviceability criteria adopted by international standards organizations and offer general acceptance guidelines based on peak acceleration thresholds. Finally, they identify design strategies that can mitigate wind-induced building motion through structural optimization, aerodynamics treatment, and vibration dissipation or absorption. -- Provided by publisher.
Keywords: Tall buildings -- Aerodynamics.; Wind-pressure.; Architecture -- Human factors.; elektronické knihy; electronic books